Renal Involvement in Rheumatoid Arthritis: Analysis of 53 Renal Biopsies - Góis, M (2017)
Background: Rheumatoid arthritis (RA) is a systemic inflammatory disorder characterized by joint inflammation, associated with autoantibody production. Renal involvement arises as a complication of treatment or can be related to the disease itself. Methods: 53 biopsies from patients with RA from 1989 to 2015 were reviewed. Histologic diagnosis, age, gender, duration of RA, drug therapy, renal function, proteinuria and haematuria were analyzed. Results: Amyloidosis was the most common renal histologic pattern (21 patients). Membranous Nephropathy (MN) was found in 12 patients, followed by Mesangial Proliferative Glomerulonephritis (n=4) and Focal and Segmental Glomerulosclerosis (n=4), IgA Nephropathy (n=3), Necrotizing Glomerulonephritis (n=3), Chronic Interstitial Nephritis (n=3), Endocapillary Proliferative Glomerulonephritis (n=2) and Minimal Change Disease (n=1). Amyloidosis correlated with long duration RA (14.9±6.66 years vs 8.84±6.37 years; p<0.001), presenting with nephrotic proteinuria in the majority of the cases (5.11±2.94 g/24h vs 3.52±2.71 g/24h p=0.03), which correlates with dominant glomerular amyloid deposition (7.0±2.28 g/24h vs 3.04±2.08 g/24h; p<0.001). In patients with MN, renal function was preserved (serum creatinine 0.83±0.21mg/dl vs 2.03±0.21mg/dl; p<0.001) and one third of the cases presented with haematoproteinuria. Disease modifying antirheumatic drugs (DMARDs) could be related with MN in six cases. Patients with Necrotizing Glomerulonephritis had a severe renal involvement, as did patients with Chronic Interstitial Nephritis. Conclusion: We found a wide spectrum of histological lesions that cannot be predicted with only clinical and laboratory findings. Thus, renal biopsy is essential to ensure correct diagnosis in RA patients who present with urinary abnormalities or deteriorated renal function.